Analysis of the spontaneous combustion and self-heating of almond shells. (1st November 2020) - Font, R.
Graphical abstract: Highlights: An increase in temperature of 26 °C was observed with sorption of water vapor. Kinetic constants for chemical oxidation were deduced by two procedures. A numerical program was used to simulate sorption of water vapor and the runaway. Runaway can be obtained after 27.1 days with 45 °C prior to water vapor sorption. Abstract: Self-heating/spontaneous combustion of almond shells in a laboratory oven with control of temperature and weight variation was studied. Two processes were considered: water vapor sorption and chemical oxidation. Different runs were made to analyze the vapor sorption at different oven temperatures, measuring weight gain due to sorption and the variation in internal temperature. With respect to oxidation kinetics, three studies were carried out: the rate of weight variation with temperature, the variation of temperature in a runaway test carried out with a spherical sample wrapped in perforated aluminum foil, and a series of runs to analyze temperatures within spherical samples. A simulation program was developed for the analysis of the sorption run and the kinetic run. In addition, the simulation program was used for the expected runaway condition for a 3–4 m diameter body, discussing the influence of the presence of water vapor.